Evaluierung von Initialisierungsmethoden für Fuzzy-k-means Algorithmen - Sauer, Malte

Tampering attacks in pairing-based cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Proceedings of Fault Tolerance and Diagnosis in Cryptography(FDTC))
In the last decade pairings have become an important, and often indispensable, ingredient in the construction of identity-based and attribute-based cryptosystems, as well as group signatures and credential systems. Consequently, the applicability of timing, power, or fault attacks to implementations of pairings is an important research topic. We will review some of the known results in this area.

RSA-Full Domain Hash Revisited - Rath, Timo
RSA Full Domain Hash ist im Zufallsorakelmodell ein EUF-CMA sicheres Signaturverfahren (existentially unforgeable under chosen-message attacks). Der Sicherheitsbeweis wird unter anderem in der Vorlesung Einführung in die Kryptographie vorgestellt. Auch bei einer genaueren Analyse verliert man bei der Reduktion einen Faktor \nicefrac{1}{q_{s}}(wobei q_{s}die Anzahl der Anfragen an das Signaturorakel darstellt), was für die Praxis in relativ großen Systemparametern (RSA-Modul) resultiert [1].Seit der Veröffentlichung von [2] wurde geglaubt, dass der Faktor \nicefrac{1}{q_{s}}optimal ist. Erst zehn Jahre später offenbarten die Autoren von [3] einen Fehler in [2] und zeigten eine bessere Reduktion allerdings unter einer etwas stärkeren Sicherheitsannahme.Die Ergebnisse aus [3] lassen sich auf PSS-Verfahren (Probabilistic Signature Scheme), das z.B. in PKCS #1 benutzt wird, übertragen und sind somit von großer Bedeutung für die Praxis. Weiterhin sind die in den Beweisen verwendete Techniken nützlich auch bei anderen kryptographischen Verfahren.In Rahmen dieser Arbeit sollen die entsprechenden Sicherheitsbeweise aufgearbeitet und dessen Auswirkungen für die Praxis analysiert werden.[1] J.S. Coron, “On the Exact Security of Full Domain Hash”, CRYPTO 2000. LNCS 1880, pp. 229-235, 2000.[2] J.S. Coron, “Optimal security proofs for PPS and other signature schemes”, EUROCRYPT 2002. LNCS 2332, pp 272-287, 2002.[3] S.A. Kakvi and E. Kiltz, “Optimal Security Proofs for Full Domain Hash, Revisited”, in EUROCRYPT 2012. LNCS 7237, pp 537-553, 2012.

A Probabilistic Expectation Maximization Algorithm for Multivariate Laplacian Mixtures - Brauer, Sascha

Analysis of Agglomerative Clustering - Ackermann, Marcel Rudolf; Blömer, Johannes; Kuntze, Daniel; Sohler, Christian (Algorithmica)

A Theoretical and Experimental Comparison of the EM and SEM Algorithm - Blömer, Johannes; Bujna, Kathrin; Kuntze, Daniel (2014 22nd International Conference on Pattern Recognition)

Constructing CCA-secure predicate encapsulation schemes from CPA-secure schemes and universal one-way hash functions - Blömer, Johannes; Liske, Gennadij
We present a new transformation of chosen-plaintext secure predicate encryption schemes with public index into chosen-ciphertext secure schemes. Our construction requires only a universal one-way hash function and is selectively secure in the standard model. The transformation is not generic but can be applied to various existing schemes constructed from bilinear groups. Using common structural properties of these schemes we provide an efficient and simple transformation without overhead in form of one-time signatures or message authentication codes as required in the known generic transformations.

A Practical Second-Order Fault Attack against a Real-World Pairing Implementation - Blömer, Johannes; Gomes da Silva, Ricardo; Günther, Peter; Krämer, Juliane; Seifert, Jean-Pierre (Proceedings of Fault Tolerance and Diagnosis in Cryptography(FDTC))
Several fault attacks against pairing-based cryptography have been described theoretically in recent years. Interestingly, none of these have been practically evaluated. We accomplished this task and prove that fault attacks against pairing-based cryptography are indeed possible and are even practical — thus posing a serious threat. Moreover, we successfully conducted a second-order fault attack against an open source implementation of the eta pairing on an AVR XMEGA A1. We injected the first fault into the computation of the Miller Algorithm and applied the second fault to skip the final exponentiation completely. We introduce a low-cost setup that allowed us to generate multiple independent faults in one computation. The setup implements these faults by clock glitches which induce instruction skips. With this setup we conducted the first practical fault attack against a complete pairing computation.

Hiding software components using functional encryption - Jochheim, Janek

Group Signature Schemes with Strong Exculpability - Bemmann, Pascal

Fujisaki-Okamoto Transformation - Lippert, Jan

Themenmodellierung zur Identifikation und Gruppierung von Spam-Webseiten - Laudemann, Stefan

Nichtapproximierbarkeitsresultate zu Radius- und Durchmesserclustering unter Verwendung von L_p-Metriken - Leder, Lennart

Practical algorithms for clustering and modeling large data sets - Analysis and improvements - Kuntze, Daniel

An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

Direct Chosen-Ciphertext Secure Attribute-Based Key Encapsulations without Random Oracles - Blömer, Johannes; Liske, Gennadij
We present a new technique to realize attribute-based encryption (ABE) schemes secure in the standard model against chosen-ciphertext attacks (CCA-secure). Our approach is to extend certain concrete chosen-plaintext secure (CPA-secure) ABE schemes to achieve more efficient constructions than the known generic constructions of CCA-secure ABE schemes. We restrict ourselves to the construction of attribute-based key encapsulation mechanisms (KEMs) and present two concrete CCA-secure schemes: a key-policy attribute-based KEM that is based on Goyal's key-policy ABE and a ciphertext-policy attribute-based KEM that is based on Waters' ciphertext-policy ABE. To achieve our goals, we use an appropriate hash function and need to extend the public parameters and the ciphertexts of the underlying CPA-secure encryption schemes only by a single group element. Moreover, we use the same hardness assumptions as the underlying CPA-secure encryption schemes.

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén

StreamKM++: A clustering algorithm for data streams - Ackermann, Marcel Rudolf; Märtens, Marcus; Raupach, Christoph; Swierkot, Kamil; Lammersen, Christiane; Sohler, Christian

Turing und Kryptografie - Blömer, Johannes (Informatik-Spektrum)
Ich beschreibe die deutsche Enigma-Verschlüsselungsmaschine und skizziere, wie sie von den Codebrechern von Bletchely Park um Alan Turing gebrochen wurde. Besonderes Augenmerk lege ich auf die Beiträge Alan Turings und die Bedeutung seiner Leistung für die Entwicklung moderner Kryptografie.

Identitätsbasierte Signaturen - Ein Sicherheitsbeweis für Signaturen auf Grundlage von Gap-Diffie-Hellman-Gruppen mit Hilfe des Forking-Lemmas - Löken, Nils

Identitätsbasierte Kryptographie - Implementierung von Paarungen für Körper der Charakteristik 2 - Haarhoff, Thomas

Attribute-basierte Verschlüsselung - Schleiter, Patrick

Bicriteria-Approximation für das k-Median-Clustering mit Bregman-Divergenzen - Böttger, Timm

The Monotone Complexity of Computing k-Clique on Random Graphs - Märtens, Marcus

Algorithms for lattice problems with respect to general norms - Naewe, Stefanie

Hardness and Non-Approximability of Bregman Clustering Problems. - Ackermann, Marcel R; Blömer, Johannes; Scholz, Christoph

How to Share a Secret - Blömer, Johannes (Algorithms Unplugged)

Solving the Closest Vector Problem with respect to Lp Norms - Blömer, Johannes; Naewe, Stefanie (arXiv:1104.3720)
In this paper, we present a deterministic algorithm for the closest vector problem for all l_p-norms, 1 < p < ∞, and all polyhedral norms, especially for the l_1-norm and the l_{∞}-norm. We achieve our results by introducing a new lattice problem, the lattice membership problem. We describe a deterministic algorithm for the lattice membership problem, which is a generalization of Lenstra's algorithm for integer programming. We also describe a polynomial time reduction from the closest vector problem to the lattice membership problem. This approach leads to a deterministic algorithm that solves the closest vector problem for all l_p-norms, 1 < p < ∞, in time p log_2 (r)^{O (1)} n^{(5/2+o(1))n} and for all polyhedral norms in time (s log_2 (r))^{O (1)} n^{(2+o(1))n}, where s is the number of constraints defining the polytope and r is an upper bound on the coefficients used to describe the convex body.

Fault attacks in pairing-based cryptography - Liske, Gennadij

Bregman Clustering for Separable Instances - Ackermann, Marcel R.; Blömer, Johannes (SWAT 2010)

Clustering for Metric and Nonmetric Distance Measures - Ackermann, Marcel R.; Blömer, Johannes; Sohler, Christian (ACM Trans. Algorithms)
Keywords: k-means clustering; k-median clustering; Approximation algorithm; Bregman divergences; Itakura-Saito divergence; Kullback-Leibler divergence; Mahalanobis distance; random sampling

On the initialization of dynamic models for speech features - Krueger, Alexander; Leutnant, Volker; Haeb-Umbach, Reinhold; Ackermann, Marcel; Blömer, Johannes (Proc. of ITG Fachtagung Sprachkommunikation. ITG, Bochum, Germany)

Efficient and Compact CCA Security from Partitioned IBKEM - Schrieb, Jonas

Engineering self-coordinating software intensive systems - Schäfer, Wilhelm; Trächtler, Ansgar; Birattari, Mauro; Blömer, Johannes; Dorigo, Marco; Engels, Gregor; O'Grady, Rehan; Platzner, Marco; Rammig, Franz; Reif, Wolfgang (Proceedings of the FSE/SDP workshop on Future of software engineering research - FoSER '10)

Smart Card basierte Berechnung einer Gruppensignatur als Teil einer biometrischen Authentisierung - Postler, Tim
Keywords: Diplomarbeit

Hierarchisches Clustering mit minimalen Cluster-Durchmessern - Schröer, Carsten

Analyse und Evaluation eines identitätsbasierten Signcryption-Verfahrens - Liske, Gennadij

Die Schwierigkeit des k-Median Clusterings für Bregman-Divergenzen - Scholz, Christoph

Algorithms for the Bregman k-Median Problem - Ackermann, Marcel Rudolf

Coresets and Approximate Clustering for Bregman Divergences - Ackermann, Marcel R.; Blömer, Johannes (Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms)

Sampling methods for shortest vectors, closest vectors and successive minima - Blömer, Johannes; Naewe, Stefanie (Theoretical Computer Science)
Keywords: Geometry of numbers; Lattices; Shortest vectors

Three-Valued Spotlight Abstractions - Schrieb, Jonas; Wehrheim, Heike; Wonisch, Daniel (FM 2009: Formal Methods)

Reliable Evidence of Data Integrity from an Untrusted Storage Service - Stern, Claudius; Adelt, Philipp; Krummel, Volker; Ackermann, Marcel Rudolf (Fourth International Conference on Networking and Services (icns 2008))

Construction and Applications of Identity-Based Encryption without Pairings - Schrieb, Jonas
Keywords: Diplomarbeit

Tamper Resistance of AES -- Models, Attacks and Countermeasures - Krummel, Volker

Analysis of Countermeasures Against Access Driven Cache Attacks on AES - Blömer, Johannes; Krummel, Volker (Selected Areas in Cryptography)

Cryptanalysis of Unbalanced RSA with Small CRT-Exponent - May, Alexander (Advances in Cryptology — CRYPTO 2002)

Low Secret Exponent RSA Revisited - Blömer, Johannes; May, Alexander (Lecture Notes in Computer Science)

Key Revocation with Interval Cover Families - Blömer, Johannes; May, Alexander (Selected Areas in Cryptography)

Dimension Reduction Methods for Convolution Modular Lattices - May, Alexander; Silverman, Joseph H. (Lecture Notes in Computer Science)

A Probabilistic Zero-Test for Expressions Involving Roots of Rational Numbers - Blömer, Johannes (Algorithms — ESA’ 98)

Approximierbarkeit durch konstante Stichproben unter Berücksichtigung verschiedener Divergenz- und Ähnlichkeitsmaße beim k-Clustering-Problem - Ziegert, Steffen

Sichere Kryptosysteme durch Zero-Knowledge - Richert, Manuel

Angriffe auf RSA-Varianten bei partiell bekannten geheimen Schlüsseln - Klein, Wiebke
Keywords: Diplomarbeit

Kryptanalyse des EAC-Protokolls biometrischer Reisepässe - Käthler, Olga
Keywords: Diplomarbeit

Analyse von verallgemeinerten RSA Polynomen mit Hilfe der Coppersmithschen Methode - Brieden, Benedikt
Keywords: Diplomarbeit

Untersuchung von Clusteringalgorithmen für die Kullback-Leibler Divergenz - Kuntze, Daniel
Keywords: Diplomarbeit

Vergleich multivariater Varianten der Methode von Coppersmith - Borghoff, Julia
Keywords: Diplomarbeit

Untersuchungen zur Sicherheit einzelner RSA Bits - Landwehr, Andreas Cord

Ein erschöpfende Suche vermeidender Algorithmus für allgemeines k-SAT - Klose, Jaroslaw

Reduktionen von CVP mit wenigen Lösungen auf CVP mit eindeutigen Lösungen - Niemeier, Martin

Behandlung von Korrekturtermen in der Methode von Coppersmith - Birkner, Stefan

Randomness and Secrecy - A Brief Introduction - Blömer, Johannes (Journal of Universal Computer Science (J.UCS))
We give a brief introduction to probabilistic encryptions. This serves as an example how randomness plays a pivotal role in cryptographic systems that satisfy advanced security concepts.

Fault Based Collision Attacks on AES - Blömer, Johannes; Krummel, Volker (Lecture Notes in Computer Science)

Wagner’s Attack on a Secure CRT-RSA Algorithm Reconsidered - Blömer, Johannes; Otto, Martin (Lecture Notes in Computer Science)

Sign Change Fault Attacks on Elliptic Curve Cryptosystems - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Lecture Notes in Computer Science)

Implementierung und Simulation von Cache-Angriffen auf AES - Funke, Rafael

Von identitätsbasierten Kryptosystemen zu CCA-Sicherheit - Schrieb, Jonas

Samplemethoden in der algorithmischen Geometrie der Zahlen - Naewe, Stefanie
Keywords: Diplomarbeit

Boomerang- und Rechteckangriff auf AES - Gorski, Michael
Keywords: Diplomarbeit

Fault Attacks and Countermeasures - Otto, Martin

A Tool Kit for Finding Small Roots of Bivariate Polynomials over the Integers - Blömer, Johannes; May, Alexander (EUROCRYPT 2005)

Partial Key Exposure Attacks on RSA up to Full Size Exponents - Ernst, Matthias; Jochemsz, Ellen; May, Alexander; de Weger, Benne (EUROCRYPT 2005)

Implementierung von wichtigen Teilen des Schoof-Elkies-Atkin Algorithmus zum Bestimmen der Punktanzahl einer elliptischen Kurve - Hornkamp, Christian

Laufzeitanalyse- und vergleich verschiedener Algorithmen zur schnellen skalaren Multiplikation auf elliptischen Kurven - Süß, Tim

Analyse von RSA mittels Coppersmith Methode - Ernst, Matthias
Keywords: Diplomarbeit

Implementierung der Coppersmith-Methode zur Untersuchung von Schwachstellen bei RSA - Spanke, Christoph
Keywords: Diplomarbeit

Provably Secure Masking of AES - Blömer, Johannes; Guajardo, Jorge; Krummel, Volker (Selected Areas in Cryptography)

A Generalized Wiener Attack on RSA - Blömer, Johannes; May, Alexander (Public Key Cryptography – PKC 2004)

Secret Exponent Attacks on RSA-type Schemes with Moduli N=p^{r}q - May, Alexander (Public Key Cryptography – PKC 2004)

Computing the RSA Secret Key Is Deterministic Polynomial Time Equivalent to Factoring - May, Alexander (Advances in Cryptology – CRYPTO 2004)

A new CRT-RSA algorithm secure against bellcore attacks - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Proceedings of the 10th ACM conference on Computer and communication security - CCS '03)

Neue Schranken für die Coppersmith-Methode über den ganzen Zahlen - Dumrauf, Dominic

Implementierung und Evaluierung eines Angriffs auf DSA - Herden, Tim

Implementierung eines Verfahrens zur Berechnung optimaler längenbeschränkter Präfix-Codes - Gesemann, Sebastian

Implementierung und Evaluation einiger Algorithmen für Kryptosysteme auf elliptischen Kurven - Gorski, Michael

New RSA Vulnerabilities Using Lattice Reduction Methods - May, Alexander

New Partial Key Exposure Attacks on RSA - Blömer, Johannes; May, Alexander (Advances in Cryptology - CRYPTO 2003)

Fault Based Cryptanalysis of the Advanced Encryption Standard (AES) - Blömer, Johannes; Seifert, Jean-Pierre (Financial Cryptography)

Asymptotische Optimalität von LZ77 bei beschränktem Speicher - Ernst, Matthias

Asymptotische Optimalität von Lempel-Ziv bei Markowprozessen - Voß, Kerstin

Markovprozesse zur Modellierung bei Codekompression - Hoppe, Ulrich
Keywords: Diplomarbeit

Implementierung eines arithmetischen Dekodierers in Java - Unterkirchner, Claudia

Tabellenbasierte arithmetische Codierung - Kuntze, Daniel

Kompressionsverlust bei arithmetischer Codierung mit endlicher Präzision - Soltenborn, Christian